Molecular Self-assembly in Nanoscience and Nanotechnology - Kilislioğlu, Ayben; Karakuş, Selcan (IntechOpen, 2017)
Self-assembly is a common principle in molecular fabrication of natural and synthetic systems and has many important applications in the fields of nanoscience and nanotechnology. This book provides clear explanations of the principles of self-assembly with the limitations along with examples and research-based results with discussion for students, researchers, and professions.